SIFO 1982: Political conditions of motorism - Swedish Institute of Public Opinion Research; Swedish Association of Auto Dealers and Service Shops; Motor Industry Association (Swedish Institute of Public Opinion Research, 1993)
The Swedish Institute of Public Opinion Research (SIFO) carried out this survey at the request of two motor organizations, the Motor Industry Association and the Swedish Association of Auto Dealers and Service Shops. The purpose of the survey was to examine opinions on how motorism should be treated by politicians and authorities. The respondents had to answer if they agreed or disagreed with statements about heavier environmental demands upon motorism, increased public revenue by heavier taxation on motorism, efforts to make it easier or harder to own and use cars. The respondents were asked about the houshold´s dependence on a car. Other questions dealt with the magazine ´Utan bilen stannar Sverige´. The magazine was shown to the respondent, who had to give an opinion on articles and advertisements. Background variables include information on age, housing, size of household, age of members of household, adult children moved out, car ownership, amount of money needed in household, personal income and household income, marital status, education, occupation, employed or self-employed, public or private sector, trade union membership, size of place of work, gender, Swedish citizenship and party preference.

Svenska Institutet för Opinionsundersökningar (SIFO) genomförde denna undersökning på begäran av två motororganisationer, Bilindustriföreningen och Motorbranschens Riksförbund. Syftet med undersökningen var att undersöka opinionen runt hur frågor om bilism ska behandlas av politiker och myndigheter. Den svarande måste svara om de är överens eller inte med olika påstående så som; strängare miljökrav på bilismen, öka statsinkomster genom ökad beskattning av bilar och olika insatser för att göra det lättare eller svårare att äga eller använda bilar. De svarande tillfrågades om hushållets beroende av bil. Andra frågor handlade om tidningen ”utan bilen stannar Sverige”. Tidningen visades för de svarande och de fick ge sin åsikt om artiklarna och reklamen. Bakgrundsvariabler inkluderar ålder, boende, storlek på hushållet, ålder på medlemmar av hushållet, vuxna utflugna barn, bilägande, inkomst, civilstånd, utbildning, yrke, anställning i privat eller offentlig sektor, medlemskap i fackförening, storlek på arbetsplats, kön, medborgarskap och partipreferens.
.
SIFO 1982: Bilismens politiska villkor
Keywords: environmental degradation; miljöförstörelse; cars; bilar; press advertising; tidningsreklam; taxation; beskattning; income; inkomst; reading (activity); läsande; Environment and conservation; Miljö och naturvård; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap